Microplástico: um contaminante invisível - Pinhatti, Victor Carrera (Universidade Federal de São Carlos, 2022)
Microplastics are small-sized plastic particles that primarily arise by the breakdown of larger plastics. They are considered ubiquitous contaminants in the environment and are found in the most diverse environmental matrices, from ocean trenches to the top of mountains, even in products that we consume and in the air we breathe. Animals and humans are constantly exposed to microplastics and these interactions bring many health hazards. This review addresses relevant issues on the subject of microplastics – regarding classification; its sources; the incidence on environmental matrices and their impact on organisms; analytical challenges; the main initiatives and solutions that aim to fight this type of contamination; and a study regarding population perception about the subject.
Microplastic: an invisible contaminant
Keywords: Microplásticos; Poluição plástica; Contaminantes ambientais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA